Murine Metatarsus Bone and Joint Collagen-I Fiber Morphologies and Networks Studied With SHG Multiphoton Imaging - Vielreicher, Martin; Bozec, Aline; Schett, Georg; Friedrich, Oliver (Frontiers in Bioengineering and Biotechnology, 2021)
Chronic inflammatory disease of bones and joints (e.g. rheumatoid arthritis, gout, etc.), but also acute bone injury and healing, or degenerative resorptive processes inducing osteoporosis, are associated with structural remodeling that ultimately have impact on function. For instance, bone stability is predominantly orchestrated by the structural arrangement of extracellular matrix fibrillar networks, i.e. collagen-I, -IV, elastin, and other proteins. These components may undergo distinct network density and orientation alterations that may be causative for decreased toughness, resilience and load bearing capacity or even increased brittleness. Diagnostic approaches are usually confined to coarse imaging modalities of X-ray or computer tomography that only provide limited optical resolution and lack specificity to visualize the fibrillary collagen network. However, studying collagen structure at the microscopic scale is of considerable interest to understand the mechanisms of tissue pathologies. Multiphoton Second Harmonic Generation (SHG) microscopy, is able to visualize the sterical topology of the collagen-I fibrillar network in 3D, in a minimally invasive and label-free manner. Penetration depths exceed those of conventional visible light imaging and can be further optimized through employing decalcification or optical clearing processing ex vivo. The goal of this proof-of-concept study was to use SHG and 2-PEF imaging to mainly characterize the fibrillary collagen organization within ex vivo decalcified normal mouse metatarsus bone and joint. The results show that the technique resolved the fibrillar collagen network of complete bones and joints with almost no artifacts and enabled to study the complex collagen-I networks with various fiber types (straight, crimped) and network arrangements of mature and woven bone with high degree of detail. Our imaging approach enabled to identify cavities within both cortical and trabecular bone architecture as well as interfaces with sharply changing fiber morphology and network structure both within bone, in tendon and ligament and within joint areas. These possibilities are highly advantageous since the technology can easily be applied to animal models, e.g. of rheumatoid arthritis to study structural effects of chronic joint inflammation, and to many others and to compare to the structure of human bone.